Un enseignement littéraire en classe inversée : les dessous d’un contrat - Marie-Sylvie Claude; Patrick Rayou (Recherches en Éducation)
This article studies a flipped classroom system in French in a secondary school, in the context of a study on the interpretation of poetry texts. A session was filmed, the students' productions and work materials were collected, the interactions between the students, who work in groups, were recorded and transcribed, and then semi-directive self-confrontation interviews were conducted with the teacher and the students. The analysis of this corpus is based by theoretical supports borrowed from the sociology of the teaching profession, from the analysis of activity and from didactics, particularly the didactics of literature. It shows that being professionally and pedagogically innovative is not always enough to ensure the learning of demanding disciplinary knowledge by all students. Flipped classroom seems to commit the teacher to three contracts that can prevent each other: the first, which can be described as "social", links her both to the school institution, whose prescriptions she wants to follow as closely as possible, and to a group of innovative professionals, which she wants to join. The second, more pedagogical in nature, leads it to train pupils who are more autonomous and capable of working in teams. The third, didactic, wants to enable students to appropriate literary texts by making a personal interpretative reading of them